Pragmalinguistic Peculiarities of Intercultural Communication in German Speaking Switzerland (Proceedings of Southern Federal University. Philology, 2019)
Svetlana S. Takhtarova (Kazan, Russian Federation)The article is devoted to the analysis of the communicative interaction of the inhabitants and the German-speaking cantons of Switzerland. Analyzed communication is complicated by a number of problems, both linguistic and cultural-conditioned. The revealed socio-cultural differences in the mutual perception of the interests of the analyzed ethnosocieties lead to the formation of stereotypes and clichés that exert their influence on communication. The revealed characteristics of the communicative style of German-speaking Switzerland made it possible to define it as a mitigative-oriented one.Key words: intercultural communication, communicative style, mitigation, ethnosocium, highly context cultures.DOI 10.23683/1995-0640-2019-1-147-154